SURGICAL TACTICS IN DISTAL LESIONS OF NERVE TRUNKS OF THE UPPER LIMBS - M.F. ODINAEV; G.M. KHODZHAMURADOV; A.KH. SHAYMONOV; M.S. SAIDOV (Avicenna Tajik State Medical University, 2019)
Objective: Optimization of the results of microsurgical reconstruction of the nerve trunks of the upper limb with their complete anatomical break at the distal level Methods: The results of reconstructions of 129 nerve trunks of the upper limbs with their complete anatomical break at the distal level, performed in 109 patients from 2012 to 2018 were analyzed. Results: In an emergency order, 47 patients with injuries of 57 nerve trunks were operated (median nerve - 26, ulnar - 23 and radial - 8), at the level of Zone I there was 14 nerve trunks, Zone II - 26, Zone III - 17 nerve trunks. In all cases, the nerve trunks were restored end-to-end. Patients with emergency lesions showed better results compared with the planned reconstruction. So, the best results were obtained in children after an emergency suture (S4, M5), which amounted to 96.5%; in adults, the percentage of good and excellent results after an emergency reconstruction was 93.7%. The results of the autonervous plasty of the nerves in their results to degrees (S3+, S4; M4-M5) were not inferior to the planned end-to-end seam of the nerve and amounted to 82-85%. Conclusion: Thus, despite the technical difficulties of identifying damaged nerve trunks at distal levels, in all cases were obtained high functional results. The developed one-step replenishment of the defect in the final segment of the nerve trunk with an autonomic transplant preparation allows not only to restore the previous anatomy but also to shorten the duration of the operation and improve the functional effectiveness of the operations.